2011
DOI: 10.1186/1744-859x-10-13
|View full text |Cite
|
Sign up to set email alerts
|

The standardised copy of pentagons test

Abstract: BackgroundThe 'double-diamond copy' task is a simple paper and pencil test part of the Bender-Gestalt Test and the Mini Mental State Examination (MMSE). Although it is a widely used test, its method of scoring is crude and its psychometric properties are not adequately known. The aim of the present study was to develop a sensitive and reliable method of administration and scoring.MethodsThe study sample included 93 normal control subjects (53 women and 40 men) aged 35.87 ± 12.62 and 127 patients suffering from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…It has been suggested by one meta-analysis that there is significant impairment of neurocognitive function with advancing age [ 8 ], while a second one reported that the difference between patients with BD and healthy controls attenuates with age, and probably this happens because the neurocognitive performance of healthy people deteriorates with age, at a rate which seems to be faster in comparison to what is observed in patients with BD [ 12 ] thus leading to a floor effect. A similar phenomenon has been observed in schizophrenia [ 327 329 ]. Another meta-analysis reported no effect for age [ 66 ]…”
Section: Reviewsupporting
confidence: 81%
“…It has been suggested by one meta-analysis that there is significant impairment of neurocognitive function with advancing age [ 8 ], while a second one reported that the difference between patients with BD and healthy controls attenuates with age, and probably this happens because the neurocognitive performance of healthy people deteriorates with age, at a rate which seems to be faster in comparison to what is observed in patients with BD [ 12 ] thus leading to a floor effect. A similar phenomenon has been observed in schizophrenia [ 327 329 ]. Another meta-analysis reported no effect for age [ 66 ]…”
Section: Reviewsupporting
confidence: 81%
“…For the test, a subject is asked to copy or draw two interlocking pentagons with the interlocking shape being a rhombus. The interpretation of PDT is usually binary, but there are several ways of interpreting PDT such as a feasible scoring for a total of 6 or 10 points [25,26], a standardized scoring for use in psychiatric populations [27], and a qualitative measure with a total of 13 points [5]. The established scores for a total of 6 points are as follows: 6 points for correct copying; 5 points for two overlapping pictures, one being a pentagon; 4 points for only two overlapping pictures; 3 points for having two figures, not overlapping; 2 points for a closed figure; and 1 point when the drawing does not have the shape of a closed figure.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown evidence for the PDT being prognostic for the assessment of visuospatial functions. The PDT has been used in the differentiation of dementia with Lewy Bodies, Alzheimer's disease, Parkinson's disease (with or without dementia), paraphrenia, schizophrenia, and obsessive compulsive disorder, with the qualitative scoring systems applied rather than using the binary scoring system [6,9,[26][27][28][29][30]. An associative study of the PDT and the CDT has also shown the PDT to be applicable as a prognostic marker in dementia with Lewy Bodies [31].…”
Section: Introductionmentioning
confidence: 99%
“…The sub-tests of the MMSE score 6 points for memory, 10 for orientation, 5 for attention, 8 for language and only 1 for praxis, which is evaluated by drawing two intersecting pentagons, in which the interconnected area should be shaped like a rhombus. 11 , 12 The interpretation of the pentagon drawing test (PDT) is usually binary, with 1 point for the correct figure.…”
mentioning
confidence: 99%
“…There are several ways of interpreting the test, besides the binary method used in the MMSE. 1 , 12 Bourke et al (1995) described an easy scoring scale for the PDT with a total of 6 points. 9 One point is given for lines drawn or attempt to draw a figure, 2 for drawing a figure, 3 for two figures not overlapping; 4 for two overlapping figures, 5 for an overlapping connection and one figure being a pentagon, and 6 for the correct copy.…”
mentioning
confidence: 99%